BRIKET ARANG CAMPURAN TANDAN KOSONG DAN DAUN KELAPA SAWIT SEBAGAI BAHAN BAKAR ALTERNATIF - Aldi Bayu Pratama; Budi Sutiya; Wiwin Tyas Istikowati (Universitas Lambung Mangkurat, 2022)
Oil palm is one of the plantation commodities that has an important role in South Kalimantan Province. The process of processing palm oil into oil from pulp and kernels (palm kernels) will produce empty oil palm fruit bunches that have not been widely used by companies. Oil palm empty fruit bunches have great potential to be converted into alternative energy such as briquettes. The purpose of this study was to analyze briquettes from a mixture of oil palm empty fruit bunches and oil palm leaves with tapioca adhesive and determine the best composition of a mixture of oil palm empty bunches and oil palm leaves to get the best quality briquettes. The results of the research from empty bunches of oil palm charcoal and oil palm leaves obtained an average moisture content of 1.70% - 5.08%, testing water content of briquettes 54.28 % - 55.73 %, density testing 0.44 g/ cm3 – 0.47 g/cm3, ash content test 1.67 % - 2.83%, calorific value test 5078.3 cal/g – 5557.6 cal/g, fuel power test 0.0113 g/d – 0 ,0117 g/d. Tests of water content, density, ash content, calorific value meet the standards of the Indonesian state, while the water content of briquettes and fuel power are not yet known for the test standards. The test results showed that the P1 treatment with 26 g OPEFB and 12 g KS leaves was the best composition in this briquette processing, the water content test produced 2.39%, the water content of the briquettes was 54.28%, the density was 0.47 g/cm3, ash 2.83% calorific value 5557.6 cal/g and combustion power 0.0114 g/d, with the results obtained during the P1 test being the best briquette composition.Kelapa sawit merupakan salah satu komoditas perkebunan yang mempunyai peranan penting di Provinsi Kalimantan Selatan. Proses pengolahan kelapa sawit menjadi minyak dari daging buah dan kernel (inti sawit) akan menghasilkan limbah TKKS yang belum banyak dimanfaatkan oleh perusahaan. TKKS mempunyai potensi yang besar untuk dikonversi menjadi energi alternatif seperti briket. Tujuan dari penelitian ini menganalisis briket dari campuran TKKS dan daun KS dengan perekat tapioka dan menentukan komposisi terbaik dari campuran TKKS dan daun kelapa sawit untuk mendapatkan kualitas briket terbaik. Hasil penelitian dari arang TKKS dan daun KS mendapatkan hasil rata-rata Kadar air 1,70 % - 5,08 %, pengujian Kadar air briket 54,28 % - 55,73 %, pengujian kerapatan 0,44 g/cm3 – 0,47 g/cm3, pengujian kadar abu 1,67 % - 2,83 %, pengujian nilai kalor 5078,3 kal/g – 5557,6 kal/g, pengujian daya bakar 0,0113 g/d – 0,0117 g/d. Pengujian Kadar air, kerapatan, kadar abu, nilai kalor memenuhi standar negara indonesia, sedangkan Kadar air briket dan daya bakar belum diketahui standar ujinya. Hasil pengujian menunjukkan bahwa perlakuan P1 dengan 26 g TKKS dan 12 g daun KS menjadi komposisi terbaik dalam pengolahan briket ini, pada pengujian Kadar air dihasilkan 2,39 % , Kadar air briket 54,28 % , kerapatan 0,47 g/cm3 , Kadar abu 2,83 % nilai kalor 5557,6 kal/g dan daya bakar 0,0114 g/d, dengan hasil yang diperoleh selama pengujian P1 menjadi kompisisi briket terbaik.